(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What are the most appropriate formats for learning content for target groups? What type of assessment framework would be most appropriate to facilitate the measurement of attainment? What types of pedagogic supports are needed to facilitate the involvement of participants (work well-being managers) into the program framework? What are the most appropriate teaching and learning methodologies for work well-being managers? Purpose: The purpose and aim of the research is to compare andragogical / pedagogical support for wellness managers’ educational programs between Slovenia and the EU and the USA. Method: With the qualitative research method, we examined the theoretical starting points of our research. We obtained information from various articles and magazines on the topic of well-being educational programs. Results: Andragogical / pedagogical support of well-being educational programs is significantly better in the US and EU than in Slovenia. In the area of support for well-being managers educational programs, Slovenia is relatively early on compared to other countries such as the EU and USA. Organization: The survey can have a positive impact on managers and society, as it has shown that educational programs for well-being managers can have a positive impact on employee satisfaction and health and, consequently, on the quality of life of both employees and their superiors. Society: The research can have a positive impact on managers and society, as it has shown that educational programs for well-being managers can have a positive impact on employee satisfaction and health and, consequently, on the quality of life of both employees and their family members. Originality: The research provides a comprehensive overview of the sample survey of all content found on the topic of andragogical / pedagogical support for well-being managers. Limitations/Future Research: The research was limited more to education and training programs, as there are not many articles on the topic of andragogical / pedagogical support for well-being managers.